2010
DOI: 10.1248/bpb.33.450
|View full text |Cite
|
Sign up to set email alerts
|

Preventative Effects of Platycodon grandiflorum Treatment on Hepatic Steatosis in High Fat Diet-Fed C57BL/6 Mice

Abstract: Non-alcoholic hepatic steatosis (NASH) is closely associated with obesity, diabetes, hyperlipidemia, and insulin resistance.1) Generally, NASH results from the accumulation of fat in the liver, primarily through excessive transport of free fatty acids from visceral adipose tissue into the liver, and from an imbalance of de novo lipid synthesis and catabolism in hepatocytes.2) Lipid-lowering drugs have been used to inhibit hepatic steatosis; however, these drugs can cause serious side effects including vomiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
2
14
0
1
Order By: Relevance
“…Quantitative measurement of hepatic lipid also demonstrated that TG concentrations in the PG-treated mice treated with EtOH were approximately 30% lower than in the EtOH control mice. In particular, S-PG treatment showed more protective effects against EtOH-induced oxidative damage than T-PG treatment, confirming our previous findings, showing preventative effects of PG on hepatic steatosis in high-fat-diet-fed mice [7]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Quantitative measurement of hepatic lipid also demonstrated that TG concentrations in the PG-treated mice treated with EtOH were approximately 30% lower than in the EtOH control mice. In particular, S-PG treatment showed more protective effects against EtOH-induced oxidative damage than T-PG treatment, confirming our previous findings, showing preventative effects of PG on hepatic steatosis in high-fat-diet-fed mice [7]. …”
Section: Discussionsupporting
confidence: 90%
“…In addition, we have recently reported a fatty liver inhibition effect of PG extract and its saponin via suppression of hepatic lipogenesis and acceleration of energy expenditure, along with the modulation of liver fatty acid synthase and carnitine palmitoyltransferase activities in high-fat-diet-fed C57BL/6 mice [7]. Moreover, hepatoprotective roles of PG have been demonstrated in various chemical- [8,9,10] and ethanol (EtOH)-induced hepatotoxicity animal models [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…As the main bioactive principles of P. grandiflorum, about 40 oleananetype saponins, composed of four types of aglycones, i.e., platycodigenin, platycogenic acid A, platyconic acid A lactone, and polygalacic acid, have been reported so far [1][2][3][4][5][6][7][8][9], and are regarded as being responsible for the various biological activities such as antitumor [10][11][12][13][14][15][16], immunomodulatory [17][18][19], hepatoprotective [20][21][22][23][24], neuroprotective [25][26][27], anti-hyperlipidemic, anti-adiposity [28,29], analgesic, antioxidant [30], anti-hyperglycemic [31] and osteogenic [32] effects.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] reported that CKS contained triterpenoid saponins, platycosides, such as deapioplatycoside E, platycoside E, deapio-platycodin D 3 , platycodin D 3 , polygalacin D 2 , platyconic acid A (PA), platycodin D 2 , platycodin D, and 2′-O-acetylpolygalacin D 2 . 9 Kwon et al reported that PA improved glucose homeostasis by enhancing insulin sensitivity in type 2 diabetic mice. 10 However, the mechanisms underlying the effects of CKS or PA as treatments for airway inflammation remain unclear.…”
Section: ■ Introductionmentioning
confidence: 99%